On-Line Estimation of All Electrical Parameters in Induction Machines subject to Stator Fault - Stocks, M.; Medvedev, A. (2007 IEEE International Conference on Control Applications, 2007)
Identification of all the electrical parameters of induction machines (IMs) is a prerequisite for successful model-based control and/or fault detection. Most of the existing identification methods of symmetrical IMs are, strictly speaking, valid only at stationary conditions, which limitation results in either poor dynamics excitation or gross approximation errors, depending on the working conditions of the motor. In this paper, the topic of identification of all electrical parameters of faulty IMs is addressed for the first time. A method for on-line observer-based estimation of all electrical parameters of IMs with faulty stator is presented aiming primarily at fault tolerant control and fault detection. The approach does not rely on any assumptions regarding the rotor angular speed and/or acceleration.